A Participatory Sensor System for Monitoring Chem and Particulate from Peat Forest Fire - Rony Teguh (Journal of Telematics and Informatics, 2018)
We have developed a low-cost participatory monitoring system for wildfire in peatland, that enables air pollutan referential parameters measurements based on a multilayer distributed parameter model with a Wido IoT platform. This is an Internet of Things (IoT) application, of which a physical object is embedded with electronics, software, sensors and GSM connectivity to allow monitoring participatory system (CO, CO2, PM10) on real-time based on cloud systems In this paper proposes a low-cost, rapid-deployment and energy-autonomous solution based on Wido IoT to improve the assessment and the understanding of air quality in developing monitoring peatland areas, thus helping policy makers and scientists to better handle air pollution. The proposal incorporates the use of a website to display collected data and processed information to empower citizens with knowledge about the air they breathe.